1996
DOI: 10.1038/379262a0
|View full text |Cite
|
Sign up to set email alerts
|

Chondrodysplasia and neurological abnormalities in ATF-2-deficient mice

Abstract: Activating transcription factor-2 (ATF-2) is a basic region leucine zipper protein whose DNA target sequence is the widely distributed cAMP response element (CRE). We report here that mice carrying a germline mutation in ATF-2 demonstrated unique actions of ATF-2 not duplicated by other ATF/CREB family members. Mutant mice had decreased postnatal viability and growth, with a defect in endochondral ossification at epiphyseal plates similar to human hypochondroplasia. The animals had ataxic gait, hyperactivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
190
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(197 citation statements)
references
References 26 publications
5
190
1
1
Order By: Relevance
“…Atf2-deficient mice display a uniform dwarfism due to reduced chondrocyte proliferation, disorganized chondrocyte columns and impaired endochondral ossification. 19 Consistent with these observations, ATF2 regulates chondrocyte proliferation by modulating cyclin D1 levels and by inhibiting hypertrophic differentiation. 20 As ATF2 is a direct target of p38 in response to TGF-b in chondrocytes, 21 it is conceivable that p38 regulates proliferating chondrocytes through this transcription factor ( Figure 1).…”
Section: Overview Of the P38 Mapk Signaling Pathwaysupporting
confidence: 54%
“…Atf2-deficient mice display a uniform dwarfism due to reduced chondrocyte proliferation, disorganized chondrocyte columns and impaired endochondral ossification. 19 Consistent with these observations, ATF2 regulates chondrocyte proliferation by modulating cyclin D1 levels and by inhibiting hypertrophic differentiation. 20 As ATF2 is a direct target of p38 in response to TGF-b in chondrocytes, 21 it is conceivable that p38 regulates proliferating chondrocytes through this transcription factor ( Figure 1).…”
Section: Overview Of the P38 Mapk Signaling Pathwaysupporting
confidence: 54%
“…Free E2F then activates transcription of genes involved in cell-cycle progression and DNA replication. 1999b), in agreement with phenotypes of reduced chondrocyte proliferation and growth retardation both in ATF-2- (Reimold et al, 1996) and cyclin D1-deficient (Fantl et al, 1995;Sicinski et al, 1995;Beier et al, 2001) mice. Subsequently, studies by a number of groups have shown that cyclin D1 expression is regulated by a large number of extracellular growth factors and hormones with known mitogenic roles in chondrocyte proliferation.…”
Section: Control Of Cell-cycle Gene Expression In Chondrocytessupporting
confidence: 63%
“…and CREB, has also been associated with effects on cortical development [120,121]. ATF2 deficient mice were shown to carry severe neurological abnormalities, with up to 50 % of neuronal loss in the cerebellum [120].…”
Section: Disruption Of Noncanonical Components Such As the Transcripmentioning
confidence: 99%
“…ATF2 deficient mice were shown to carry severe neurological abnormalities, with up to 50 % of neuronal loss in the cerebellum [120]. Years later, Ackermann et al were able to produce mice with a neuronal-specific ATF2 deletion that enabled its study in the CNS.…”
Section: Disruption Of Noncanonical Components Such As the Transcripmentioning
confidence: 99%